Responses of Soil Profile Hydrology, Structure and Microbial Respiration to Organic Amendments Under Different Tillage Systems on the Loess Plateau - Lili Zhao; Lusheng Li; Xiangjie Chen; Yanbin Li; Jiankun Ge; Xiaowen Wang (Agronomy)
The combined effects of tillage and organic amendments on microbial respiration and its contribution to soil hydraulic conductivity are still uncertain in the 0–40 cm layer of a loess soil. We conducted a two-year field experiment to explore the effects of organic amendments, tillage and their interaction on soil microbial respiration, aggregate stability, pore parameters, and hydraulic conductivity on the Loess Plateau. Three tillage methods (conventional tillage (CT), deep tillage (DT) and no tillage (NT)) plus five fertilizer treatments (mineral fertilizer (control) alone and along with 20 t ha−1 wheat straw (MWS), wheat husk (MWH), farmyard soil (MFS) and bioorganic fertilizer (MBF)) were set up as experimental treatments. The findings demonstrated that the organic amendments significantly increased the soil microbial respiration and saturated hydraulic conductivity compared to the control in the 0–10 cm and 10–20 cm layers. Soil microbial respiration had indirect effects on hydraulic conductivity by improving the water aggregate stability and macroporosity. Additionally, the interaction effects of tillage and organic amendments on the pore and hydrological parameters were significant in the 20–40 cm layer. NT-MBF resulted in the greatest saturated hydraulic conductivity, which was directly correlated with the soil’s strong pore organization. Given the issue of subsurface soil compaction in our study area, it is recommended that local farmers adopt NT-MBF to enhance the soil’s microbial, structural and hydrological properties.